1975
DOI: 10.1136/gut.16.11.894
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids and colonic motility in the rabbit and the human.

Abstract: SUMMARY Colonic motor activity was initiated by infusions of bile salts into the caecum or rectum of the anaesthetized rabbit. Primary bile acids were examined proximally and distally in the colon and elicited marked motor responses. Since dihydroxy bile acids are known to be potent inhibitors of electrolyte and water absorption in the colon, the secondary bile acid deoxycholic acid, the dihydroxy compound most related to cholic acid which is the main bile acid in the rabbit, was examined distally and was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
80
1

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(84 citation statements)
references
References 8 publications
3
80
1
Order By: Relevance
“…The increase motility in this study supported also by Kirwan et al (1975), who found that the abnormally high quantities of primary BAs in the colon cause diarrhea not only by inhibiting the absorption of water and electrolytes, but also by eliciting colonic motor activity.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The increase motility in this study supported also by Kirwan et al (1975), who found that the abnormally high quantities of primary BAs in the colon cause diarrhea not only by inhibiting the absorption of water and electrolytes, but also by eliciting colonic motor activity.…”
Section: Discussionsupporting
confidence: 72%
“…Early in vivo studies showed that BAs either stimulate motility or have no effect (Feldman and Gibaldi, 1968;Kirwan et al, 1975 andFalconer et al, 1980). In vitro researches demonstrated that BAs inhibit contractions of rabbit and guinea pig intestine (Armstrong et al, 1993;Romero et al, 1993;Poole et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Controlled trials on the use of appetite suppressants such as amphetamines have shown a variety ofundesirable side effects including central nervous stimulation, addiction, toxicity, euphoria and even ineffectiveness. The use of amphetamines has been discouraged but fenfluramine, an analogue of amphetamine, has become widely used as an anti-obesity agent devoid of central nervous stimulation (Munro, Seaton and Duncan, 1966;Le Douarec and Niven, 1970). There are reports of its beneficial effects on hyperlipidaemia (Pawan, 1969;Bliss, Kirk and Newall, 1972), on hypercholesterolaemia (Tomlinson, Lines and Greenfield, 1975), and on hyperglycaemia (Turtle, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Bile acids have a direct secretory effect on colonic enterocytes, 3 and indirectly induce a secretory response by stimulating mast cells or intrinsic neural arcs. 4,5 In addition, the introduction of bile acids into the human sigmoid colon and rectum stimulates colonic motility, 6 and chenodeoxycholate significantly accelerates colon transit time in healthy subjects. 7 A failure to reabsorb bile acid was also suggested to be a cause of diarrhea owing to excess bile acids entering the colon.…”
Section: Introductionmentioning
confidence: 99%